1999
DOI: 10.1086/315149
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoside Analogues Achieve High Concentrations in Seminal Plasma: Relationship between Drug Concentration and Virus Burden

Abstract: Human immunodeficiency virus (HIV) can be transmitted in semen from a man to his sexual partners. Antiretroviral drugs are likely to affect the amount of HIV-1 in semen and perhaps transmission of the virus. The concentrations of zidovudine, lamivudine, and HIV-1 RNA in blood and seminal plasma were measured in 9 HIV-positive men over Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 15 publications
2
41
0
Order By: Relevance
“…The reason for the very high concentrations observed in cat 3 at first dose is uncertain. In general, variability in parent drug concentration was similar to what has been described in humans (25). The formation of semen is complex and the composition of ejaculated fluid is highly modified as it passes through secretory tissues.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…The reason for the very high concentrations observed in cat 3 at first dose is uncertain. In general, variability in parent drug concentration was similar to what has been described in humans (25). The formation of semen is complex and the composition of ejaculated fluid is highly modified as it passes through secretory tissues.…”
supporting
confidence: 76%
“…Indeed, after an extended time without ejaculation (Fig. 3), concentrations were usually higher than those observed during the two 12-h collection periods, indicating that in cats, like humans (1,13,25), accumulation in this biological compartment extends beyond a single dosing interval. Systemic drug exposure over a dosing interval in the cats, as measured by AUC (Table 1) was positively correlated with seminal plasma excretion (Spearman's correlation coefficient, 0.67, P ϭ 0.03), suggesting that approximately 40% of the variability in semen drug concentrations can be explained by systemic exposure to ZDV and 3TC.…”
mentioning
confidence: 96%
“…Concentrations in semen should be interpreted with caution, since the percentage of protein binding of the drugs in this compartment is unknown. Regarding CSF, the presence of high NRTI concentrations in semen also makes it difficult to draw conclusions about the efficacies of PIs for the suppression of viral replication in semen (23 In lymphoid tissue, residual HIV-1 RNA was detected in all LN tissue samples of patients who had previously received suboptimal regimens, even when HIV-1 RNA was undetectable in plasma for 2 to 3 years. All three PIs were detectable in LN tissue samples, but with wide differences in the concentration in LN tissue/concentration in plasma ratio, suggesting a better penetration for indinavir.…”
Section: Discussionmentioning
confidence: 99%
“…NRTIs ought not to penetrate the MGT because of lipid insolubility, yet NRTIs are the most penetrable ARV class, suggesting the involvement of drug sequestration or active transport (Reddy et al 2003;Taylor et al 2003a) (Table 2). Seminal zidovudine and lamivudine levels are twice that in blood (Henry et al 1988;Pereira et al 1999Pereira et al , 2000Reddy et al 2002). The observed seminal zidovudine level may result from drug binding to seminal protein (Anderson et al 2000).…”
Section: Nucleoside Reverse Transcriptase Inhibitors (Nrtis)mentioning
confidence: 93%
“…• The stability of ARVs after heat inactivation of HIV-1 in plasma or semen (3 h at 58°C) for safe handling was not discussed (Pereira et al 1999Anderson et al 2000); • Validated methods were reported for plasma analysis but not semen. Some authors diluted semen with plasma (1:1), presumably to reduce matrix effects; however, evidence for the appropriateness of this practice was not presented (van Praag et al 2000(van Praag et al , 2001aTaylor et al 1999Taylor et al , 2001bSankatsing et al 2002;Solas et al 2003; (Wang et al 2007).…”
Section: Sparidans Et Al (2000mentioning
confidence: 99%